Dinoflagellates cyst assemblage concerning trophic index for eutrophication from major ports along the west coast of India. (March 2022) - Rodrigues, R.V.; Patil, J.S.; Anil, A.C.
Abstract: An overview of dinoflagellates cysts assemblage is presented as a trophic index for three monsoon-influenced estuarine and marine ports along the Indian coast. The cyst distribution (including harmful species) showed a trend of highest abundance and species number in highly eutrophicated estuarine (Cochin-south) followed by medium (New-Mangalore-central) and low (Kandla-north) levels of eutrophicated marine ports. The investigation revealed four new species in the region ( Bitectatodinium spongium, Gonyaulax elongatum, Brigantedinium sp. and potential harmful species Blixaea quinquecornis -cyst similar to planktonic). Autotrophs dominance in the highly productive Cochin and New-Mangalore ports reveals that, in eutrophic systems, heterotrophs need not always be dominant. The indicator taxa ( Polykrikos, Protoperidnium, and Lingulodinium ) presence in high density indicated a eutrophic system. This study concludes cyst (species numbers/Fisher-α index/indicator species) as potential eutrophication proxies and emphasizes greater harmful-algal-bloom risks in the high trophic-index ports (Cochin and New-Mangalore). Highlights: Studied dinoflagellate cysts assemblage from monsoon influenced Indian major ports. Cochin, Mangalore & Kandla ports formed high, medium & low level of eutrophication. Cyst abundance & species richness increased with eutrophication (Eut) levels. Autotrophic cysts dominance, diversity, species richness form potential Eut proxies High-medium eutrophicated ports harbour more cysts of potential harmful species.